PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Oktafia, Yufenti (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2010)
Earning managements is a management action in the process of preparing financial statements to influence the level of earnings that is displayed. Earnings management is one factor that can reduce the credibility of financial statements. Add to bias earnings management in the financial statements and can interfere with the use of a trusted financial reports profit figures as a result of these engineering profit numbers without engineering. Corporate governance is a concept proposed to improve business performance through supervision or monitoring management performance and ensuring accountability of management to the stakeholders with a framework based on rules. The concept of corporate governance as proposed for the achievement of corporate management more transparent to all users of financial statements. If this concept is applied properly it is expected that economic growth will continue to rise in line with the transparency of corporate management a better and will benefit many parties. Detection possibility of earnings management in the financial statements, examined through the use of estimates of total accruals. Total accruals consist of nondiscretionary accrual and discretionary accruals. Earnings management occurs because of opposition from various interested parties on the financial statement information, which interested parties on financial statements information that is internal and external parties. Conflicts of interest that occurs is minimized by a mechanism that is capable of aligning the interests of external and internal parties. Agency theory suggests that earnings management issues can be eliminated with the supervision of their own through good corporate governance.Keywords: corporate governance, discretionary accrual